HUBUNGAN PENGAWASAN DENGAN DISIPLIN KERJA PEGAWAI PADA DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN DHARMASRAYA - Asri Inayati (Jurnal Bahana Manajemen Pendidikan, 2014)
This research aimed to see work discipline, supervisory and work discipline between supervisory with work discipline in Dinas Pendidikan pemuda dan Olahraga Kabupaten Dharmasraya. The population are all of employees in Dinas Pendidikan pemuda dan Olahraga Kabupaten Dharmasraya amount to 59 people and the samples are 39 people that determined based on Proportional Stratified Random Sampling technique. Instrument used was a questionnaire were formulated based on likert scale and analyzed by Product Moment correlation. The results are significant relationship between supervisory with work discipline in Dinas Pendidikan pemuda dan Olahraga Kabupaten Dharmasraya. Key Word : work discipline, supervisory